Membran Nanofiltrasi untuk Aplikasi Pemisah Zat - Yohana Ivana Kedang (Fakultas Pertanian, Universitas Timor, 2019)
The mechanism of nanofiltration separation is largely based on the size and difference in diffusion rates for organic molecules and electrostatic effects for ions. However, because the molecules are not more charged, the mechanism based on molecular size is more widely used. Nanofiltration membranes operate without phase changes and usually have a high rejection of multivalent inorganic salts and small organic molecules at moderate pressure. This makes the separation process very competitive in terms of selectivity and cost when compared to traditional separation. Nanofiltration membranes have been applied in various industrial sectors namely wastewater treatment, pharmaceutical processes and biotechnology, and food engineering. This article is expected to provide ideas and recommendations regarding the innovation of making nanofiltration membranes for dyestuff waste separators.